Role of cranberry juice in preventing recurrent urinary tract infections in the pediatric population - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Urinary tract infections (UTIs) are common in the pediatric population, a majority being caused by E. coli. Recurrent UTI not only results in disruption of the daily routine but can also lead to renal scarring. An important bacterial property leading to UTI is the presence of adhesion factors that decrease bacterial washout. The most common intervention used to prevent recurrent UTI is long-term and low-dose antibiotics. Cranberry products, available in India, have also been used as prophylactic intervention.